Thrombogenicity of sirolimus-eluting stents and bare metal stents: evaluation in the early phase after stent implantation - Walter, Thomas; Rey, Katja-Simone; Wendel, Hans Peter; Szabo, Sebastian; Süselbeck, Tim; Dempfle, Carl-Erik; Borggrefe, Martin; Swoboda, Stefanie; Beyer, Martin E.; Hoffmeister, Hans Martin (In vivo, 2010)
Thrombogenicitiy of drug-eluting stents is a matter of controversial debate. The aim of this study was to evaluate the thrombogenicity of sirolimus-eluting stents (SES) compared to bare metal stents (BMS) in a standardised in vitro model.
Gesehen am 04.10.2023
Kein DOI vorhanden